The Routledge companion to interdisciplinary studies in singing. - Heydon, Rachel, 1971-; Fancourt, Daisy; Cohen, Annabel J., 1947- (Routledge Companion to Interdisciplinary Studies in Singing Ser., 2020)
The Routledge Companion to Interdisciplinary Studies in Singing, Volume III: Wellbeing explores the connections between singing and health, promoting the power of singing--in public policy and in practice--in confronting health challenges across the lifespan. These chapters shape an interdisciplinary research agenda that advances singing's theoretical, empirical, and applied contributions, providing methodologies that reflect individual and cultural diversities. Contributors assess the current state of knowledge and present opportunities for discovery in three parts: Singing and Health Singing and Cultural Understanding Singing and Intergenerational Understanding In 2009, the Social Sciences and Humanities Research Council of Canada funded a seven-year major collaborative research initiative known as Advancing Interdisciplinary Research in Singing (AIRS). Together, global researchers from a broad range of disciplines addressed three challenging questions: How does singing develop in every human being? How should singing be taught and used to teach? How does singing impact wellbeing? Across three volumes, The Routledge Companion to Interdisciplinary Studies in Singing consolidates the findings of each of these three questions, defining the current state of theory and research in the field. Volume III: Wellbeing focuses on this third question and the health benefits of singing, singing praises for its effects on wellbeing.